A REDUCED KINETIC MECHANISM FOR PROPANE FLAMES - Andreis, G. S. L.; Gomes, R. S.; De Bortoli, A. L. (Revista de Engenharia Térmica, 2012)
Propane is one of the simplest hydrocarbons that can be a representative of higher hydrocarbons used in many applications. Therefore, this work develops a ten-step reduced kinetic mechanism among 14 reactive species for the propane combustion. The model is based on the solution of the flamelet equations. The equations are discretized using the second-order space finite difference method, using LES (Large-Eddy Simulation). Obtained results compare favorably with data in the literature for a propane jet diffusion flame. The main advantage of this strategy is the decrease of the work needed to solve the system of governing equations.